2015
DOI: 10.3233/cbm-150505
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of insulin receptor mRNA splice variants as a diagnostic tumor marker in breast cancer

Abstract: The results demonstrate an increased IR-A:IR-B ratio in all clinical stages of breast cancer. Thus, IR-A:IR-B ratio may have a diagnostic biomarker utility in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…No correlations were found between IR levels and age, body weight, menopausal status, and nodal involvement of breast cancer patients [10]. Aljada et al showed that mRNA levels of IR were significantly higher in cancer patients presented with advanced clinical stage of the disease compared to early stages [44]. As our findings demonstrate, a favorable prognostic impact for IR expression in breast cancer tissues and IR expression may be perceived as a marker of differentiation [43].…”
Section: Discussionsupporting
confidence: 43%
“…No correlations were found between IR levels and age, body weight, menopausal status, and nodal involvement of breast cancer patients [10]. Aljada et al showed that mRNA levels of IR were significantly higher in cancer patients presented with advanced clinical stage of the disease compared to early stages [44]. As our findings demonstrate, a favorable prognostic impact for IR expression in breast cancer tissues and IR expression may be perceived as a marker of differentiation [43].…”
Section: Discussionsupporting
confidence: 43%
“…Moreover, IR-A content in HR ER+ cancers was higher than IGF-1R content. In addition, an increased IR-A mRNA expression with a decreased IR-B expression results in an increased IR-A:IR-B ratio, as was detected in human breast cancer ( Table 1 ) [ 30 , 31 ]. The IR isoforms expression is different in distinct breast cancer ER+ subtypes that have a different response to hormone treatment and a different prognosis.…”
Section: Deregulation Of Ir In Cancermentioning
confidence: 91%
“…The second and most important finding, herein described, is the characterization of GL56 anti-IR aptamer. As recently emerged, IR, in addition to regulate important aspects of cellular physiology, 35 , 36 , 37 is overexpressed and overactivated in several cancers 19 , 20 and interfering with its expression (by shRNA) results in the inhibition of tumor growth and metastasis. 13 These data, together with the involvement of the receptor in drug resistance, 21 , 22 strongly indicate that therapeutic strategies directed against the receptor may represent an important challenge in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated expression of the IR in its embryonic isoform A and overactivation of the receptor have been demonstrated in several kinds of cancer. 19 , 20 In addition, it has been reported that IR may have an important role in the resistance to various anticancer therapies 21 , 22 and to anti-IGF-1 receptor drugs, 23 strongly indicating the potential of IR targeting. 24 So far, available drugs, generated to inhibit IGF-1R, have generally no inhibiting activity on IR and anticancer strategies specifically targeting the IR are still lacking, thus representing an important challenge in oncology.…”
Section: Introductionmentioning
confidence: 99%